Are there potential costs for humility in a pluralistic democracy?: A longitudinal investigation of immigrants in the New Zealand attitudes and values study - McLaughlin, Aaron T.; Davis, Don E.; Lee, Yejin; Woo, Hee Chan; Coleman, Jamian; Bulbulia, Joseph; Osborne, Danny; Sibley, Chris G. (Frontiers in Psychology, 2024)
In this longitudinal study, we examine the potential costs and benefits of humility for well-being and civic trust among immigrants in a pluralistic democracy. With data from 14,864 immigrant participants from a nationwide random sample in New Zealand, we used multilevel modeling to examine the associations general humility (i.e., honesty-humility modesty) had with well-being (life satisfaction and meaning) and civic trust (trust in police) over time in contexts with varying levels of ethnic deprivation and perceived religious discrimination. We hypothesized that (a) humility would correlate positively with well-being and civic trust (Hypothesis 1), (b) these associations would be attenuated in the contexts where perceptions of ethnic deprivation and religious discrimination are high (Hypothesis 2), and (c) these interaction effects would become more pronounced when cultural identities are salient (Hypothesis 3). Multilevel modelling revealed partial support for these hypotheses. Although humility correlated positively with well being and trust in police over time, the two-way and three-way interactions did not yield substantial support for Hypotheses 2 and 3, respectively. The context of religious discrimination did, however, marginally attenuate the positive association between humility and trust in police. Collectively, these results demonstrate that humility is associated with multiple benefits to well being and civic trust and has few—if any—potential drawbacks.